Removal of Ammonium from Aqueous Solution Using Natural and Modified Dalian Clinoptilolite - Fu, Kan; Li, Zhong; Xia, Qibin; Zhong, Tongchang (Asian Journal of Chemistry, 2012)
The removal of ammonium from aqueous media using Chinese Dalian clinoptilolite has been investigated. To improve the ammonium exchange of the clinoptilolite, its modifications in aqueous NaCl solution at different temperatures and under different power levels of ultrasonication have been tested. The ammonium-exchange isotherms of the clinoptilolite have been determined. The effects of solution pH and the different modifications of the clinoptilolite on ammonium exchange have been further studied. The results showed that a pseudo-second-order model gave a better correlation for all of the kinetic data as compared to Vermeulen's model or an intraparticle diffusion model. The optimal pH of solutions for ammonium exchange with clinoptilolite has been identified to be between 3 and 9. Natural clinoptilolite soaked in aqueous NaCl solution at 98 ºC had the highest sodium content, leading to an improved ammonium-exchange capacity. The ammonium-exchange capacity of clinoptilolite could be improved by increasing the temperature at which it was soaked in aqueous NaCl solution, but it could not be improved by increasing the power level of ultrasonication continuously. All of the ammonium-exchange equilibrium isotherms, with both natural and modified clinoptilolite, conformed well to the Freundlich model.